2014
DOI: 10.1002/nau.22570
|View full text |Cite
|
Sign up to set email alerts
|

Bladder function after radical hysterectomy for cervical cancer

Abstract: Nerve-sparing techniques appear to improve bladder function without compromising overall survival. Studies comparing the effects of nerve-sparing radical hysterectomy with standard surgery yielded encouraging results in respect of postoperative lower urinary tract function. Clinical trials with a long period of follow-up are required for better comprehension of the complex pathophysiology of bladder dysfunction after radical hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 46 publications
(77 reference statements)
4
49
0
4
Order By: Relevance
“…No contamos con evaluación de la función sexual o defecatoria en nuestro estudio. Las mismas se pueden ver minimizadas al realizar la técnica de preservación nerviosa (28) . En nuestra serie hubo dos lesiones vesicales que se resolvieron sin inconvenientes por vía laparoscópica con sutura laparoscópica.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…No contamos con evaluación de la función sexual o defecatoria en nuestro estudio. Las mismas se pueden ver minimizadas al realizar la técnica de preservación nerviosa (28) . En nuestra serie hubo dos lesiones vesicales que se resolvieron sin inconvenientes por vía laparoscópica con sutura laparoscópica.…”
Section: Discussionunclassified
“…La tasa de recurrencia media para cáncer de cuello en estadios precoces es de 5%, siendo esta similar en la vía tradicional laparotómica y en la vía de mínima invasión (22,28) . En nuestra serie contamos con un seguimiento medio mayor a dos años, siendo este el momento de mayor riesgo de recurrencia.…”
Section: Discussionunclassified
“…Indeed, urinary incontinence is frequently reported after radical pelvic surgery. 7,17 All gynecologists operating in the pelvis should realize that preservation of the SHP, HN, pelvic splanchnic nerves, and IHP does not automatically warrant sufficient postoperative bladder function when the vesical plexus could still be damaged.…”
Section: Discussionmentioning
confidence: 99%
“…precipitate urine leakage, denoting the insufficiency of continence mechanisms related to such structures. Nonneurogenic causes of pelvic floor or sphincter injury (Doughty & Burns, 2006;Drake et al, 2016;Gordon, Shorter, Isodi, & Moldwin, 2017;Khandelwal & Kistler, 2013;Laterza et al, 2015;Thiruchelvam et al, 2015), and weakness or relaxation of the urethral sphincter due to injury or neurological disease was exclusively associated condition to this ND (Doughty & Burns, 2006;Drake et al, 2016), although other conditions have also been identified in the literature review. Post-prostatectomized men (Milsom et al, 2017) and men with abdominal obesity (Li, Xu, Nie, Li, & Mao, 2017) were populations highlighted as being exclusively at risk for this ND.…”
Section: )mentioning
confidence: 94%